Estimating the release of chemical substances from consumer products, textiles and pharmaceuticals to wastewater. (January 2022) - Gustavsson, M.; Molander, S.; Backhaus, T.; Kristiansson, E.
Abstract: Chemical emissions from households originate from a wide range of sources and results in highly diverse mixtures. This makes traditional monitoring based on analytical chemistry challenging, especially for compounds that appear in low concentrations. We therefore developed a method for predicting emissions of chemicals from households into wastewater, relying on consumption patterns from multiple data sources. The method was then used to predict the emissions of chemical preparations, chemicals leaching from textiles and prescription pharmaceuticals in Sweden. In total we predicted emissions of 2007 chemicals with a combined emission of 62, 659 tonnes per year – or 18 g/person and day. Of the emitted chemicals, 2.0% (w/w) were either classified as hazardous to the environment or were both persistent and mobile. We also show that chemical emissions come from a wide range of uses and that the total emission of any individual chemical is determined primarily by its use pattern, not by the total amount used. This emphasizes the need for continuous updates and additional knowledge generation both on emission factors and excretion rates as well as a need for improved reporting on the intended use of individual chemicals. Finally, we scrutinize the model and its uncertainty and suggest areas that need improvement to increase the accuracy of future emission modelling. We conclude that emission modelling can help guide environmental monitoring and provide input into management strategies aimed at reducing the environmental effect caused by hazardous chemicals. Graphical abstract: Image 1 Highlights: Emission were estimated for 2007 unique chemicals. From Swedish consumers the total emission was estimated to be 62, 659 tonnes per year. The estimates suggest emissions of approximately 18 g of chemicals per person and day. 96% (by weight) of emissions are estimated to originate from chemical preparations. 2% (w/w) are hazardous to the environment or human health, or persistent and mobile.